Interplanar Growth of 2D Non‐Van der Waals Co2N‐Based Heterostructures for Efficient Overall Water Splitting. Issue 44 (7th October 2020) - Jiang, Jingyun; Yan, Pengfei; Zhou, Yannan; Cheng, Zhenfeng; Cui, Xinwei; Ge, Yifei; Xu, Qun
Abstract: The design and synthesis of 2D heterostructured materials for water splitting are normally based on van der Waals (vdW) nanosheets, but this approach is gradually approaching a performance ceiling in terms of activity and stability. Herein, a novel heterostructured system is explored based on 2D non‐vdW and conductive nanosheets. Notably, the interplanar growth of 2D non‐vdW Co2 N nanosheets is realized between graphene layers in the current collector of carbon fiber papers (CPs), generating an interlocking structure within CPs. The exposed surface of Co2 N nanosheets possesses a high surface energy that anchors highly active CoNC, forming 2D CoNC@Co2 N heterostructures outside CPs. This integrated electrocatalytic system bridged by non‐vdW Co2 N nanosheets presents a low overpotential of 1.52 V and an excellent stability of 280 h, which outperform most bifunctional and nonprecious‐metal‐based electrocatalysts in alkaline media, owing to the nature of 2D non‐vdW nanosheets and the formation of strong and conductive connections among CoNC, nanosheets, and CPs. Abstract : 2D non‐van der Waals Co2 N‐based heterostructures exhibit excellent activity (1.52 V) and superior stability (280 h) for overall water splitting, due to the nature of 2D non‐vdW nanosheets and the formation of strong and conductive bonding among CoNC, the nanosheets, and carbon‐fiber‐paper substrates.